2015
DOI: 10.4172/2376-127x.1000215
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Babies Born to Mothers with Oligohydramnios: A Two Years’ Experience

Abstract: BackgroundPreterm delivery and sub-optimal fetal growth are associated with each other and affect both mother and infant. Our aim was to determine (i) whether there are detectable differences in DNA methylation between early and late gestation and (ii) whether changes in DNA methylation from entry are associated with spontaneous preterm delivery with and without reduced fetal growth.MethodsWe conducted a case-control study nested within a large prospective cohort. Gene specific methylation was measured by Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
0
7
0
1
Order By: Relevance
“…Analysis of methylated DNA by BS sequencing was completed as described previously. 22 Briefly, BS conversion was performed for 100 ng purified gDNA with EZ DNA Methylation Gold kit (Zymo Research) according to the manufacturer’s instructions. TRPA1 CGI was amplified by PCR with primers whose sequence may be provided upon request.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of methylated DNA by BS sequencing was completed as described previously. 22 Briefly, BS conversion was performed for 100 ng purified gDNA with EZ DNA Methylation Gold kit (Zymo Research) according to the manufacturer’s instructions. TRPA1 CGI was amplified by PCR with primers whose sequence may be provided upon request.…”
Section: Methodsmentioning
confidence: 99%
“…The fetus may suffer from external shocks and maternal vaginal microbial infections. 31 If oligohydramnios occurs in the first trimester, the fetus may be partially adhered to the amniotic membrane or suffer amniotic band syndrome which causes body impairment. If oligohydramnios occurs in the late stage of pregnancy, the lack of amniotic fluid may force the fetus to rest in an unnatural position, which is likely to cause musculoskeletal malformations and hypoplasia, resulting in growth retardation and LBW.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, oligohydramnios was the only risk factor that could be significantly correlated with AKI incidence in the neonates. Fedakar et al 13 and Asgharnia et al 14 also observed that mothers with oligohydramnios had an increased incidence of perinatal asphyxia and renal dysfunction in their neonates. Antenatal chronic hypoxia causes accelerated placental aging with loss of placental nutritive function and a reduction in amniotic fluid.…”
Section: Discussionmentioning
confidence: 96%